Bridging the cultural divide? Exploring school pupils' perceptions of medicine. Issue 6 (14th February 2019) - Alexander, Kirsty; Cleland, Jennifer; Nicholson, Sandra
Abstract : Context: Literature published around a decade ago demonstrated that UK individuals from non‐traditional groups may not consider, or aspire to, medicine because of sociocultural barriers and instead may perceive medicine as 'not for the likes of me'. Since this time, the UK higher education landscape has undergone significant change, with an increased emphasis on student choice and widening access (WA) initiatives. Consequently, the present study looks anew at the perceptions of medicine held by school pupils from non‐traditional backgrounds to assess whether sociocultural factors remain a major barrier to medicine. Methods: Focus groups were conducted with 71 high‐achieving school pupils in their penultimate or final years (aged 16–18 years). Participants attended UK state‐funded schools engaged with medical school WA initiatives. Transcripts were analysed thematically using a data‐driven approach. Themes were then interpreted through the conceptual lens of the 'reflexive habitus', an adapted version of Bourdieu's classic concept. Results: Participants did not perceive that sociocultural differences would deter them from aspiring to, or pursuing, the career of their choice. Some participants identified their 'different' background as a strength to bring to medicine. They reported that intrinsic motivators (personal interest and fulfilment) were most important in their own career choices. When asked what they believed might have motivated current medical students for the career, participants debated the role of extrinsic motivators (high status and income) versus intrinsic ones. 'Hot knowledge' (social contacts) from within medicine helped some participants reconcile any clash in perceived values and better imagine themselves in the profession. Conclusions: These non‐traditional school pupils from schools engaged with WA initiatives appear to have embraced the belief that medicine is for anyone with the appropriate desire and ability, regardless of background. Furthermore, some pupils reported that some aspects of their 'difference' (diversity) could help enrich the workforce and patient care. Abstract : Given the prevalence of widening access initiatives, the authors re‐visit the perspective of non‐traditional students to query how things have changed.